2021
DOI: 10.1186/s13007-021-00828-0
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for the application of exogenous phytohormones to the grass leaf base protodermal zone to improve grass leaf epidermis development research

Abstract: Background The leaf epidermis functions to prevent the loss of water and reduce gas exchange. As an interface between the plant and its external environment, it helps prevent damage, making it an attractive system for studying cell fate and development. In monocotyledons, the leaf epidermis grows from the basal meristem that contains protodermal cells. Leaf protoderm zone is covered by the leaf sheath or coleoptile in maize and wheat, preventing traditional exogenous phytohormone application me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Moreover, osmotic stress was shown to inhibit leaf expansion growth by increased auxin action via the ARF family of auxin response activators, indicating that auxin also mediates drought stress responses in the shoot [84]. Auxin may also positively impact drought tolerance by limiting stomatal density and controlling stomatal aperture [85].…”
Section: Auxin Promotes Drought Stress Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, osmotic stress was shown to inhibit leaf expansion growth by increased auxin action via the ARF family of auxin response activators, indicating that auxin also mediates drought stress responses in the shoot [84]. Auxin may also positively impact drought tolerance by limiting stomatal density and controlling stomatal aperture [85].…”
Section: Auxin Promotes Drought Stress Tolerancementioning
confidence: 99%
“…On the other hand, decreased cytokinin content was associated with increased membrane integrity under drought stress conditions and increased ABA sensitivity [93]. While cytokinin treatments have been shown to increase stomatal density in leaves, cytokinin is also known to counteract the effect of ABA on stomatal closure [85,100]. Recently, it was discovered that this cytokinin/ABA crosstalk regulates osmotic stress tolerance by regulating the global control of protein synthesis rates [101].…”
Section: Cytokinin Negatively Regulates Drought Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Booker et al (2003) and Cai et al (2018) reported that indole-3-acetic acid (IAA) did not directly inhibit the growth of lateral buds because IAA applied at shoot apices could not enter inside the lateral buds. Although, information on the mechanism of hormonal absorption and translocation in plant tissues has not been widely reported, many studies nevertheless, found a positive correlation between growth and enhanced exogenous levels of 6-BAP which had tremendous effects on endogenous cytokinin content (Yuan et al, 2019;Li et al, 2021;Zhang et al, 2021). Liu and Zhang (2017), reported foliar application of exogenous 6-BAP to improve plant drought stress resistance by increasing the rate of photosynthesis, stomatal conductance, and transpiration rates, reducing yield losses up to 46% in soybean.…”
Section: Role Of -Bap In Soybeanmentioning
confidence: 99%
“…The transcriptional network responsible for this subdivided development was also revealed (Gao, Guo, Chen, et al, 2021a). The leaf epidermis plays an important role in regulating transpiration and is the first line of defense against biological and abiotic invasion (Li et al, 2021). In addition, the epidermis not only forms a protective barrier against the environment (Yeats & Rose, 2013), but also plays a role in growth control (Czesnick & Lenhard, 2015).…”
Section: Introductionmentioning
confidence: 99%